Pengaruh Pola Makan Balita, Pengetahuan Gizi Ibu dan Pendapatan Keluarga Terhadap Risiko Stunting : (Suatu Kasus Pada Risiko Stunting Balita di Kecamatan Rancakalong Kabupaten Sumedang) - Ulfah, Nurul (Fakultas Pertanian Universitas Winaya Mukti, 2025)
Stunting is a growth and developmental disorder in children caused by chronic malnutrition and recurrent infections, characterized by a height or length below the standard. The main cause of stunting is long-term (chronic) malnutrition that can occur from prenatal stages through the first 1000 days of life. Besides nutritional factors, many other factors contribute to stunting, including childcare practices, dietary patterns, sanitation, economic status, parental education, and maternal knowledge. Stunting is a critical issue requiring immediate attention due to its adverse effects on children, including growth impairment, reduced cognitive and mental abilities, susceptibility to diseases, and future productivity. This study aims to investigate the influence of toddler dietary patterns, maternal nutrition knowledge, and family income on the risk of stunting in the Rancakalong subdistrict of Sumedang District. Methodology: This is a quantitative descriptive study using multiple linear regression analysis. The study population consists of mothers with toddlers in the Rancakalong subdistrict of Sumedang District. The sample size is 96, determined using the Slovin's formula. Results: The study found significant influences (sig < 0.05) of Toddler Dietary Patterns (X1) and Maternal Nutrition Knowledge (X2) on Stunting Risk in the Ranckalong subdistrict of Sumedang District. However, Family Income (X3) showed non-significant results (sig > 0.05) concerning stunting risk. The coefficient of determination in this study is 0.61, indicating that 61% of stunting risk can be explained by Toddler Dietary Patterns, Maternal Nutrition Knowledge, and Family Income variables, while 39% is explained by other variables beyond the independent variables of this study. Conclusion: Toddler Dietary Patterns, Maternal Nutrition Knowledge, and Family Income jointly have a simultaneous effect on Stunting Risk. However, the partial influences indicate that only Toddler Dietary Patterns and Maternal Nutrition Knowledge significantly affect Stunting Risk in Rancakalong subdistrict, while Family Income does not have a significant influence. Keywords : Toddler Dietary Patterns, Maternal Nutrition Knowledge, Family Income, Stunting.